2022
DOI: 10.3389/fpsyt.2021.784569
|View full text |Cite
|
Sign up to set email alerts
|

Growth in the Aftermath of Psychosis: Characterizing Post-traumatic Growth in Persons With First Episode Psychosis in Singapore

Abstract: Experiencing first episode psychosis (FEP) is a highly traumatic life event. However, there is evidence to show that the outcome of psychosis is more nuanced than was conventionally thought. Young persons with FEP can grow from the experience of psychosis. In this study, we aim to characterize post-traumatic growth (PTG) in persons with FEP over 1 year. A total of 99 FEP clients receiving services from an early psychosis intervention team in Singapore were recruited. The PTG Inventory, among other scales, like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…Though they may not have had a clear and positive plan for their own future, they expressed a willingness to assist individuals with SMI in the future. This finding is consistent with studies on posttraumatic growth and stress-related growth in mental illness conducted by recent studies (Lee et al, 2022 ; Ng et al, 2021 ; Slade et al, 2019 ), which highlighted changes in relationships and increased sensitivity. Since empathy is fundamentally a response to observing another person’s experiences (Furnham & Sjokvist, 2017 ), it supports the argument that psychological and mental illness experiences can contribute to improved empathy.…”
Section: Discussionsupporting
confidence: 92%
“…Though they may not have had a clear and positive plan for their own future, they expressed a willingness to assist individuals with SMI in the future. This finding is consistent with studies on posttraumatic growth and stress-related growth in mental illness conducted by recent studies (Lee et al, 2022 ; Ng et al, 2021 ; Slade et al, 2019 ), which highlighted changes in relationships and increased sensitivity. Since empathy is fundamentally a response to observing another person’s experiences (Furnham & Sjokvist, 2017 ), it supports the argument that psychological and mental illness experiences can contribute to improved empathy.…”
Section: Discussionsupporting
confidence: 92%
“…Total scores range from 10 to 50, with higher scores indicating greater overall religious commitment. The RCI-10 has generally been shown to have good reliability (Worthington et al, 2003); in this study sample, it was shown to have a high internal consistency of Cronbach's α = 0.96 (Lee et al, 2022). For these analyses, RCI-10 total scores were used.…”
Section: Samplementioning
confidence: 93%
“…The data analysed in this study was collected as part of a larger study on posttraumatic growth as experienced by patients with psychosis (Lee et al, 2022). Participants ( n = 99) were recruited from the Early Psychosis Intervention Programme (EPIP) at the Institute of Mental Health, Singapore from April 2018 to May 2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in PTG studies involving psychosis (i.e. Jordan et al , 2019; Lee et al , 2022) and COVID-19 (i.e. Celdrán et al , 2021; Ellena et al , 2021), a large proportion of research indicates the greatest degree of psychological change within the domain of “appreciation of life”.…”
Section: Introductionmentioning
confidence: 99%